A critical assessment of the design issues in e‐commerce systems development. Issue 4 (30th March 2020) - Ehikioya, Sylvanus A.; Guillemot, Eric
Abstract: Designers of electronic commerce (e‐commerce) transaction system applications face many challenges; some are old while others are emerging because of the emerging nature of the e‐commerce domain itself. This article examines the critical design challenges at different stages of the design process of e‐commerce applications. The high‐level designs have a large number of new issues specific to Web applications. Among them, the security and networking problems are the most determinant for the success of the applications. At the detailed design level, the languages and the user interface are major concerns. The user interface, specific to the Web, forces designers to redefine the traditional concept of the end user for the more appropriate customer‐centric concept. This is necessary to address the needs of consumers and for the survival of e‐commerce businesses. In addition, we also examine issues bothering the development team and the e‐commerce environment. Designers experienced in non‐Web applications can be more successful at developing e‐commerce applications if they address the issues we identified in this article in a creative way. Abstract : This article examines the critical design challenges at different stages of the design process of e‐commerce applications. We also examine issues bothering the development team and the e‐commerce environment. Designers experienced in non‐Web applications can be more successful at developing e‐commerce applications if they address the issues we identified in this article in a creative way.